Implementasi Load Cell sebagai komponen Alat Rehabilitasi Disfungsi Sendi Lutut - Heru Sumarno, Agus Sukoco; Mandayatma , Eka; Radianto, Doni; Saukani, Imam (Elposys: Jurnal Sistem Kelistrikan, 2024)
Knee joint fractures caused after surgery or other activities that cause knee dysfunction require a rehabilitation process. Knee dysfunction means the knee joint cannot be bent/moved at the desired angle. Because the function of the knee is so important in relation to human activities, it is necessary to immediately carry out rehabilitation measures for a perfect return. Rehabilitation in this case can be done with weight training. In this research, loading for rehabilitation will be designed using load cell-based electronic engineering for the desired load, because the equipment used so far works manually.The research began with inventorying component requirements, designing the circuit, compiling a process algorithm, functional testing, calibration and data collection. The research data is a function of weight on movement, in this case motorbikes. The output of the research is a control circuit prototype to regulate load-based motor movement.The equipment specifications are produced with a loading capacity limit of 5 kg with a change step of 250 grams.